QSAR study of platelet-activating factor (PAF) receptor binding antagonist - Abdullah, Nor Hayati; Ibrahim Ali , Noorbatcha; Ling, Sui Kiong (2013)
The aim of this study was to find the structure activity relationship between the platelet-activating factor (PAF) receptor binding antagonist activity and the psychochemical properties of flavonoids 1-11 by using quantum chemical QSAR approach. The semi-empirical method quantum method was used to optimize the molecular structures of the flavanoids and various quantum chemical descriptors were calculated from the optimized structures. Heuristic and multi-linear regression methods were used to determine the correlation between the quantum chemical properties and the experimental PAF receptor binding inhibitory activity. The best correlation equation was obtained using three descriptors and multi-linear correlation method with R2= 0.9632